Silver and fluoride penetration and biofilm suppression on root dentin following various silver diamine fluoride application strategies - Phitakthanaakul, Pheeratas; Senawongse, Pisol; Pudla, Matsayapan; Saikaew, Pipop (Mahidol Dental Journal, 2025)
Objectives: The aim of this study was to evaluate silver and fluoride penetration and their effects on biofilm, using different silver diamine fluoride (SDF) applications. Materials and Methods: Thirty caries-free maxillary premolars were sectioned into 1 mm-thick root dentin slabs. The area of 2x2 mm root dentin window was made with nail varnish. A total of 40 specimens were prepared for element analysis, and 20 were sterilized for biofilm assessment. Specimens were divided into four groups based on SDF application: Group 1: distilled water (control), Group 2: SDF 10 seconds, Group 3: SDF 10 seconds + light curing 20 seconds, and Group 4: SDF 60 seconds. Specimens underwent energy dispersive X-ray spectroscopy (EDX) and scanning electron microscopy (SEM) for silver and fluoride penetration from 0-500 μm analysis. The remaining 20 specimens were divided into four groups according to SDF applications and incubated for multispecies biofilm (Streptococcus mutans, Lactobacillus rhamnosus, and Actinomyces naeslundii) at 24 hours after SDF application, then analyzed using confocal laser scanning microscopy with live/dead staining. Biovolume and cell viability were quantified. Two-way ANOVA was used for silver and fluoride penetration. One-way ANOVA was used to analyze biovolume and cell viability. Results: At the surface (0 μm depth), groups 3 and 4 showed significantly higher atomic percentages of silver (At%Ag: p<0.001), while no significant differences were observed at other depths and application methods. All experimental groups (Groups 2–4) exhibited higher atomic percentages of fluorine (At%F) than the control, but no clear trend was identified among them. Biofilm assessments indicated that SDF applications reduced biovolume and cell viability (p<0.001), with more significant reductions in light-cured and prolonged application time groups. Conclusions: This study provides key insights into how light curing can enhance silver retention and biofilm suppression within a shorter application time.